2013
DOI: 10.1111/jasp.12059
|View full text |Cite
|
Sign up to set email alerts
|

Existential motive underlying cosmetic surgery: A terror management analysis

Abstract: Why do people consider cosmetic surgery? Based on the terror management theory, the present research identifies an existential motive: Through cosmetic surgery, people can symbolically defend against their death anxiety. A correlational study and an experiment showed that death terror, whether operationalized as individual differences in fear of death or experimentally manipulated mortality salience, was associated with stronger acceptance of cosmetic surgery. This association was absent among participants who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…They may also make changes in physical appearance. This might account for why some people may undertake cosmetic surgery -by making themselves appear younger, it might help reduce the anxiety that death might be approaching (Tam, 2013).…”
Section: Death Anxiety: the Fear Of Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…They may also make changes in physical appearance. This might account for why some people may undertake cosmetic surgery -by making themselves appear younger, it might help reduce the anxiety that death might be approaching (Tam, 2013).…”
Section: Death Anxiety: the Fear Of Deathmentioning
confidence: 99%
“…Thus, the most common response to the thought of one's death, or the death of other loved ones, is fear. For almost 30 years researchers employing the social psychological perspective have used terror management theory to explain death anxiety (Burke, Martens, & Faucher, 2010;Tam, 2013. Terror management theory (Solomon, Greenberg, & Psyzczynski, 1991; posits that both humans and other animals have an instinctive drive for selfpreservation.…”
Section: Death Anxiety: the Fear Of Deathmentioning
confidence: 99%
“…As noted above, the specific contingencies of a behavior can be on account of experimental procedures or individual differences. At the outset, we reasoned that pairing the exercising bike with mortality salience would strengthen physical activity as a viable route to self-esteem maintenance; however, consistent with prior research (Hansen et al, 2010;Tam, 2013;Wong et al, 2016), this might be especially true for people who already derive self-esteem from fitness. To that end, we assessed whether baselines levels of fitness contingent self-esteem, collected during a mass testing time period before participants came to the research lab, moderated these effects.…”
Section: Discussionmentioning
confidence: 61%
“…However, it may not be so linear. Indeed, Tam () found that the association between cosmetic surgery acceptance and both death anxiety trait and contextual mortality salience was particularly strong among high explicit self‐esteem participants. This result suggests that cosmetic surgery is undergone as a proactive practice to preserve self‐esteem (see also Delinsky, ; Goin & Goin, ).…”
Section: A Psychosocial Theoretical Framework For Investigating Intenmentioning
confidence: 99%